The- Law Implementation of Body Shaming that Leads to Sexual Harassment Against Women in Social Media - Ricky Shandy; Retno Dewi Pulung Sari (IHSA Institute, 2023)
Beauty is the main reason for someone, especially a woman, to look stunning. A woman who feels beautiful uploading a photo of herself often experiences body shaming in the form of hate speech and bad comments through social media. It leads to sexual harassment. The Indonesian government passes the Violence Crime Act on Sexual Harassment (TPKS) which is expected to be a brand-new breakthrough in the Indonesian legal system. As well as the existence of restorative justice, it is hoped that it will also be one of the breakthroughs in the legal world by seeking a solution by emphasizing re-election to its original state. Not many women are well-aware of this new regulation. It is hoped that more awareness of this regulation to be well-spread, and that it can create determent effects for perpetrators of sexual harassment against women on social media. Using normative juridical qualitative method in compiling this research, the writer explains how effective the new regulation is for Indonesian women.